Knowledge and attitude towards post-partum insertion of intra uterine devices among pregnant women attending antenatal clinic at a tertiary care teaching hospital - Vyas, Himanshu; T., Deviga; ., Mamta (International Journal Of Community Medicine And Public Health, 2020)
Background: Post-partum insertion of intra uterine devices (PPIUCD) increased the accessibility for women following childbirth. In India, the most women in the first year postpartum have an unmet need for family planning due to lack of information and fear of complications. The aim of the study is to assess the knowledge and attitude regarding postpartum insertion of intra uterine devices, among antenatal mothers. Methods: Descriptive cross-sectional survey design. The antenatal mothers, gestational age above 20weeks, registered at AIIMS Jodhpur were selected by purposive sampling technique. A total of 183 subjects were recruited for the data collection. A structured knowledge questionnaire and 5 point Likert scale was used to assess the knowledge and attitude among regarding PPIUCD respectively. Informed consent was taken from each participant prior to data collection and descriptive and inferential statistics were employed to analyze the data. Results: Majority (57.4%) of the subjects had fair knowledge, 24.6% had poor knowledge, only 18% with good knowledge and none of them had excellent in knowledge regarding PPIUCD. Majority (64.5%) had neutral attitude, 33.3% had positive attitude and 2.2% had negative attitude towards PPIUCD. A positive correlation found between the knowledge and attitude (r=0.509) regarding PPIUCD. Pregnant women’s education was found to be significantly associated with knowledge and attitude regarding PPIUCD. Conclusions: The findings underline that majority of the antenatal mothers having lack of knowledge and less positive attitude regarding PPIUCD. Hence there is a need to hence the comprehensive PPIUCD literacy and highly positive attitude among antenatal mothers in order to meet the family planning needs.